Phase-Field Simulation and Dendrite Evolution Analysis of Solidification Process for Cu-W Alloy Contact Materials under Arc Ablation - Hanwen Ren; Jian Mu; Siyang Zhao; Junke Li; Yateng Yang; Zhiyun Han; Zexi Xing; Qingmin Li (Metals)
Cu-W alloys are widely used in high-voltage circuit breaker contacts due to their high resistance to arc ablation, but few studies have analyzed the microstructure of Cu-W alloys under arc ablation. This study applied a phase-field model based on the phase-field model developed by Karma and co-workers to the evolution of dendrite growth in the solidification process of Cu-W alloy under arc ablation. The process of columnar dendrite evolution during solidification was simulated, and the effect of the supercooling degree and anisotropic strength on the morphology of the dendrites during solidification was analyzed. The results show that the solid–liquid interface becomes unstable with the release of latent heat, and competitive growth between dendrites occurs with a large amount of solute discharge. In addition, when the supercooling degree is 289 K, the interface is located at a lower height of only 15 μm, and the growth rate is slow. At high anisotropy, the side branches of the dendrites are more fully developed and tertiary dendritic arms appear, leading to a decrease in the alloy’s relative density and poorer ablation resistance. In contrast, the main dendrites are more developed under high supercooling, which improves the density and ablation resistance of the material. The results in this paper may provide a novel way to study the microstructure evolution and material property changes in Cu-W alloys under the high temperature of the arc for high-voltage circuit breaker contacts.